In Search of Public Support Toward Cultural Pluralism Enacted by Chinese “Potehi” Puppetry Acculturation - Ni Wayan Suarmini; Kartika Nuswantara; Aurelius Ratu; Niken Prasetyawati; Dyah Satya Yoga Agustin (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
Indonesia is a country built from cultural pluralism and multi ethnicities. “Bhineka Tunggal Ika” is a paradigm propagated to build community’s mindset to build understanding among people from different traits, cultures, and religions. Diversities have potentials to increase social tensions, crises, and extremism that are all threatened the community resilience. At the same time, diversities continue to increase together with the increased number of migrations. As such, cultures embedded to migrated people and acculturate into the local people and cultures. One of the products of acculturation is Chinese Glove Puppetry, or Wayang Potehi. There have been so many studies investigating the acculturation process and the efforts of the enthusiasts to make this culture accepted by the local people. This is a good phenomenon as the understanding multiculturalism leading to strong resilience. However, there is a lack of data of how the commitment of public either from a group of local people and Chinese descendants in Indonesia accepting this acculturation and accepting this as a part of cultural pluralism. The present study surveyed 102 respondents revealing their commitment toward pluralism. The findings revealed driving and inhibiting factors. National ideology, the urge to unite, and external dangers are driving forces, while inadequate appreciation of pluralism, tolerance, and social disparity are inhibiting forces.